PEMANFAATAN WAKTU BAGI MANUSIA DALAM KARYA SENI GRAFIS - Zico Farlin, Dr. Budiwirman, M.Pd., Yofita Sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2018)
The aims of the creating of this work is How to visualize timeless discipline in graphic art. Ths is work of out contain, with objects and objects in surreal style using serigraphy techniques through canvas media.The method the creating of this graphic artwork through several stages: a) preparation, b) Elaboration c) Synthesis d) Concept Realization, and the finishing process of the work e) Art Exhibition. Ten works presented representing the theme raised, containing issues related to Time, and its effects, contains about the phenomenon that occurs around the life of the author from the academic circles to the wheels of government bureaucracy where it will affect the self and the general public. There ten works are: 1) Academic, 2) Rubber Clock, 3) Times is money, 4) Forgotten, 5) No Focus, 6) Regret, 7) Wasted, 8) No Purpose, 9) Pursued Time, and 10) Less Motivation.Kata Kunci: Waktu, Seni Grafis, Serigrafi